2014
DOI: 10.1109/tsp.2014.2345635
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Analysis of the Variance in Gaussian Belief Propagation

Abstract: Gaussian belief propagation (BP) has been widely used for distributed estimation in large-scale networks such as the smart grid, communication networks, and social networks, where local measurements/observations are scattered over a wide geographical area. However, the convergence of Gaus-sian BP is still an open issue. In this paper, we consider the convergence of Gaussian BP, focusing in particular on the convergence of the information matrix. We show analytically that the exchanged message information matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Therefore, we have MSE G M P (v −1 ) > MSE G M P (v l −1 ) due tov −1 >v l −1 . As a result, we have the inequality (a) in (38). Hence, we obtain Corollary 2.…”
Section: Iteration #7mentioning
confidence: 60%
“…Therefore, we have MSE G M P (v −1 ) > MSE G M P (v l −1 ) due tov −1 >v l −1 . As a result, we have the inequality (a) in (38). Hence, we obtain Corollary 2.…”
Section: Iteration #7mentioning
confidence: 60%
“…In [5], [6], necessary and sufficient conditions for asymptotic convergence of the Gaussian BP algorithm are studied. The purpose of this paper is to study the convergence rate of the Gaussian BP algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Three sufficient conditions for the convergence of GaBP in loopy graphs are known: diagonaldominance [25], [26], convex decomposition [24] and walksummability [27]. Recently, a necessary and sufficient variance convergence condition of GaBP is given in [28]. For the GMPID based on the pairwise graph, a sufficient condition of the mean convergence is given in [31] and it is shown that 1) the covariance matrices definitely converge, 2) if they converge, the means of GMPID coincide with the true marginal means.…”
Section: Introductionmentioning
confidence: 99%